The Ferrante letters : an experiment in collective criticism - Chihaya, Sarah; Emre, Merve; Hill, Katherine, 1982-; Richards, Jill C., 1983-; Marcus, Sara, 1977-; Brostoff, Marissa; Loofbourow, Lili; Swanson, Cecily; Schiller, Amy (Literature now., 2020)
"Like few other works of contemporary literature, Elena Ferrante's Neapolitan novels found an audience of passionate and engaged readers around the world. Inspired by Ferrante's intense depiction of female friendship and women's intellectual lives, four critics embarked upon a project that was both work and play: to create a series of epistolary readings of the Neapolitan Quartet that also develops new ways of reading and thinking together. In a series of intertwined, original, and daring readings of Ferrante's work and her fictional world, Sarah Chihaya, Merve Emre, Katherine Hill, and Jill Richards strike a tone at once critical and personal, achieving a way of talking about literature that falls between the seminar and the book club. Their letters make visible the slow, fractured, and creative accretion of ideas that underwrites all literary criticism and also illuminate the authors' lives outside the academy. The Ferrante Letters offers an improvisational, collaborative, and cumulative model for reading and writing with others, proposing a new method the authors call collective criticism. A book for fans of Ferrante and for literary scholars seeking fresh modes of intellectual exchange, The Ferrante Letters offers incisive criticism, insouciant riffs, and the pleasure of giving oneself over to an extended conversation about fiction with friends"--